Combined Transcriptomic and Lipidomic Analysis Reveals Dysregulated Genes Expression and Lipid Metabolism Profiles in the Early Stage of Fatty Liver Disease in Rats - Zhai, Ruina; Feng, Lei; Zhang, Yu; Liu, Wei; Li, Shengli; Hu, Zhiyong (Frontiers in Nutrition, 2021)
Nonalcoholic fatty liver disease (NAFLD) develops from simple steatosis (NAFL) to nonalcoholic steatohepatitis (NASH), then potentially develops into liver cirrhosis, is a serious threat to human health. Therefore, investigating the formation and development mechanism of NAFLD is of great significance. Herein, we successfully established an early model of NAFLD by feeding rats with a high-fat and choline-deficient diet. Liver tissue samples were obtained from rats in the fatty liver model group (NAFL) and normal diet control group (CON). Thereafter, we performed transcriptome and lipidomic analysis. Transcriptome results revealed that 178 differentially expressed genes were detected in NAFL and CON groups; out of which 105 genes were up-regulated, 73 genes were down-regulated and 8 pathways were significantly enriched. A total of 982 metabolites were detected in lipidomic analysis; out of which 474 metabolites were significantly different, 273 were up-regulated, 201 were down-regulated and seven pathways were significantly enriched. Based on the joint analysis, three common enrichment pathways were found, including cholesterol metabolism, fat digestion and absorption, metabolic pathways. Overall, in the early stage of NAFLD, a small number of genetic changes caused a strong response to lipid components; the strongest reflection was glycerides and glycerophospholipids. A significant increase in fatty acid uptake accompanied by cholesterol metabolism is the most prominent metabolic feature of the liver in the early stage of NAFLD. In the early stage of fatty liver, the liver had shown the characteristics of NASH.